L-type calcium channel modulates mechanosensitivity of the cardiomyocyte cell line H9c2. (May 2019) - Takahashi, Ken; Hayashi, Shogo; Miyajima, Mari; Omori, Marei; Wang, Jing; Kaihara, Keiko; Morimatsu, Masatoshi; Wang, Chen; Chen, Jian; Iribe, Gentaro; Naruse, Keiji; Sokabe, Masahiro
Graphical abstract: Highlights: L-type Ca channels are crucial in mechanosensitive Ca response in heart cells. Both external and internal sources are involved in stretch induced Ca response (SICR). Knockdown of L-type Ca channel diminished SICR in rat cardiomyocytes. Blocker of L-type calcium channel diminished mechanosensitivity of ex-vivo rat heart. Abstract: The application of mechanical stimuli to cells often induce increases in intracellular calcium, affecting the regulation of a variety of cell functions. Although the mechanism of mechanotransduction-induced calcium increases has not been fully resolved, the involvement of mechanosensitive ion channels in the plasma membrane and the endoplasmic reticulum has been reported. Here, we demonstrate that voltage-gated L-type calcium channels play a critical role in the mechanosensitive calcium response in H9c2 rat cardiomyocytes. The intracellular calcium level in H9c2 cells increased in a reproducible dose-dependent manner in response to uniaxial stretching. The stretch-activated calcium response (SICR) completely disappeared in calcium-free medium, whereas thapsigargin and cyclopiazonic acid, inhibitors of sarcoendoplasmic reticulum calcium ATPase, partially reduced the SICR. These findings suggest that both calcium influx across the cell membrane and calcium release from the sarcoendoplasmic reticulum are involved in the SICR. Nifedipine, diltiazem, and verapamil, inhibitors of L-type calcium channels, reduced the SICR in a dose-dependent manner. Furthermore, small interfering RNA against the L-type calcium channel α1c subunit diminished the SICR dramatically. Nifedipine also diminished the mechanosensitivity of Langendorff-perfused rat heart. These results suggest that the SICR in H9c2 cardiomyocytes involves the activation of L-type calcium channels and subsequent calcium release from the sarcoendoplasmic reticulum.